Percanggahan waktu mustajab doa hari jumaat: Analisis kaedah Tarjīḥ Al-Suyūṭῑ menurut perspektif hadis Mawḍu‘ī - Mohd Nor Adzhar Ibrahim; Muhammad Akmalludin Mohd Hamdan; Roshimah Shamsudin; Mohd Solleh Ab Razak; Wan Khairul Aiman Wan Mokhtar (USIM PRESS, 2025)
There are differing perspectives among Islamic scholars regarding the determination of the auspicious time for supplication (du‘a) on Fridays. There exist over 30 viewpoints, with the widely accepted opinion being that the auspicious time is after the ‘Asr prayer. These differences arise due to the general nature of the hadiths concerning the auspicious time for supplication on Fridays. Based on these hadiths, al-Suyūṭī opined that the auspicious time for supplication on Fridays occurs when the Imam stands during the iqāmah before the Friday prayer. This view of al-Suyūṭī is articulated in his work, al-Lum‘ah fī Khaṣā’iṣ Yawm al-Jumu‘ah, which compiles hadiths on the virtues of Fridays. Thus, this study aims to examine al-Suyūṭī's determination of the auspicious time on Fridays as outlined in his work, based on the concept of mawḍū‘ī hadith. To achieve this objective, a library research methodology grounded in qualitative research with a content analysis design was thoroughly employed in the data collection process, followed by analysis using inductive and deductive methods. The findings of the study indicate that in selecting this particular time, al-Suyūṭī applied several steps characteristic of mawḍū‘ī hadith study, including the initial compilation of relevant hadiths, followed by their analysis, and subsequently establishing correlations among the hadiths. Although al-Suyūṭī’s view differs from the more widely accepted opinions, he is found to have his unique methodology in determining the auspicious time for supplication on Fridays. This methodology is grounded in several strong evidence derived from hadith, which he employs as his arguments.